2019
DOI: 10.3389/fnhum.2019.00101
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate and Sustained Positive Effects of Meditation on Resilience Are Mediated by Changes in the Resting Brain

Abstract: While recent studies have explored the maintenance of the effect of meditation on stress resilience, the underlying neural mechanisms have not yet been investigated. The present study conducted a highly controlled residential study of a 4-day meditation intervention to investigate the brain functional changes and long-term effects of meditation on mindfulness and resilience. Thirty participants in meditation practice and 17 participants in a relaxation retreat (control group) underwent magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 54 publications
(65 reference statements)
3
16
0
1
Order By: Relevance
“…Our meta-analysis does not include non-controlled (single-arm) trials due to the presence of confounding factors. One of the important confounders is called the “vacation effect.” This effect is reported in some studies that show the non-intervention group also had peripheral BDNF changes during follow-up (Epel et al, 2016 ; Kwak et al, 2019 ). The BDNF changes suggesting a vacation effect, refers to the temporary improvements in health and psychological well-being after taking a vacation, which soon fade after work resumption (Goldberg et al, 2018 ).…”
Section: Methodssupporting
confidence: 67%
“…Our meta-analysis does not include non-controlled (single-arm) trials due to the presence of confounding factors. One of the important confounders is called the “vacation effect.” This effect is reported in some studies that show the non-intervention group also had peripheral BDNF changes during follow-up (Epel et al, 2016 ; Kwak et al, 2019 ). The BDNF changes suggesting a vacation effect, refers to the temporary improvements in health and psychological well-being after taking a vacation, which soon fade after work resumption (Goldberg et al, 2018 ).…”
Section: Methodssupporting
confidence: 67%
“…On the whole, such findings were expected, given previous empirical evidence linking resilience to social (Arewasikporn et al 2019) and temporal (Zheng et al 2019) embeddedness. One surprising finding, however, was the absence of an association between body awareness and resilience, a hypothesis derived from evidence of the role of interoception in appraisal and adaptive behaviour (Haase et al 2015) and success in its use as an intervention target for improving resilience (Kwak et al 2019). There may be two potential reasons for this disparity in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interoceptive awareness has direct bearing on resilience as it is implicated in adaptive behaviour (Perchtold et al 2019). Conversely, abnormal body perception is implicated in depression (Wiebking et al 2010) and low body awareness has been associated with low resilience (Haase et al 2016), with body awareness interventions successfully found to foster resilience (Hwang et al 2018;Kwak et al 2019).…”
mentioning
confidence: 99%
“…Recent research has shown that anatomic and physiologic changes in the developing brain also occur in response to positive stimuli and events (Kwak et al, 2019 ; Tomlinson et al, 2016 ), and that the brain shows growth and healing following a significant traumatic event (Fujisawa et al, 2015 ; Nakagawa et al, 2016 ). These and other observations led to the study of PCEs alongside ACEs, shifting the focus to a relationship-based, Science of the Positive (Linkenbach, 2020 ), approach which touches on all levels of the social-ecological system (Bronfenbrenner, 2009 ).…”
Section: Purposementioning
confidence: 99%
“…Recent research has pointed to PCEs as protective and mitigating factors against the effects of ACEs and toxic stress (Bethell et al, 2019 ). Neurobiological studies, showing physical and functional changes in the brain in response to positive stimuli, suggest a physiologic mechanism for this phenomenon (Fujisawa et al, 2015 ; Kwak et al, 2019 ; Lake et al, 2017 ; Nakagawa et al, 2016 ; Nenert et al, 2018 ; Tomlinson et al, 2016 ). Mitigating toxic stress is especially urgent during the pandemic, as families and children experience social isolation, financial difficulty, and other disruptions to their daily lives, factors which also increase risk of child maltreatment.…”
Section: Assessmentmentioning
confidence: 99%